2018
DOI: 10.1080/08830185.2018.1506780
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and species-specific conservation of toll-like receptors in terrestrial vertebrates

Abstract: Toll-like receptors (TLRs) are known for their essential roles in promotion of innate immunity and induction of adaptive immunity through recognition of pathogen-associated molecular patterns (PAMPs) or danger associated molecular patterns (DAMPs). TLR genes are excellent models for the study of the selective pressure enforced by microorganisms on the host genome. Phylogenetic analyses have shown that interactions between pathogens and immune systems have changed during evolution. Selective pressure for mainte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 96 publications
0
9
0
Order By: Relevance
“…TLRs are typically under purifying selection with signatures of positive selection, mostly in cell-surface TLRs rather than in intracellular TLRs. This indicates the conserved feature of the viral pathogens, detected on intracellular TLRs, compared with the escaping bacterial pathogens, detected on the cell surface TLRs [87]. Nevertheless, for coronaviruses, studies have shown that different (cell-surface or endosomal) TLRs are triggered.…”
Section: Ii) Cell-surface Tlrsmentioning
confidence: 92%
“…TLRs are typically under purifying selection with signatures of positive selection, mostly in cell-surface TLRs rather than in intracellular TLRs. This indicates the conserved feature of the viral pathogens, detected on intracellular TLRs, compared with the escaping bacterial pathogens, detected on the cell surface TLRs [87]. Nevertheless, for coronaviruses, studies have shown that different (cell-surface or endosomal) TLRs are triggered.…”
Section: Ii) Cell-surface Tlrsmentioning
confidence: 92%
“…Studies in non-model organisms have mainly adopted the candidate gene approach, with MHC and TLR genes being popular in a broad range of jawed vertebrates, from fish to amphibians, birds and mammals (Bagheri & Zahmatkesh, 2018;Brouwer et al, 2010;Minias & Vinkler, 2022;O'Connor et al, 2019;Wilson, 2017).…”
Section: How To Approach Immune G Ene He Terog Eneit Y In E Volutiona...mentioning
confidence: 99%
“…Studies in non‐model organisms have mainly adopted the candidate gene approach, with MHC and TLR genes being popular in a broad range of jawed vertebrates, from fish to amphibians, birds and mammals (Bagheri & Zahmatkesh, 2018 ; Brouwer et al, 2010 ; Minias & Vinkler, 2022 ; O'Connor et al, 2019 ; Wilson, 2017 ). Although all jawed vertebrates possess mostly overlapping core immunomes, it is evident that the final composition of immune genes and gene copy numbers can differ considerably between vertebrate classes and orders, and even within orders and families (Fiddaman et al, 2022 ; Meyer‐Lucht et al, 2016 ; Minias et al, 2019 ; O'Connor & Westerdahl, 2021 ; Těšický & Vinkler, 2015 ; Velová et al, 2018 ; Wang et al, 2012 ).…”
Section: How To Approach Immune Gene Heterogeneity In Evolutionary St...mentioning
confidence: 99%
“…More generally, PRRs are highly conserved and found in a diverse range of animal species. They provide the foundation upon which the hosts’ immune response to pathogens has evolved (e.g., Masoumeh and Zahmatkesh 2018). PRRs account for many other families of sensors beside TLRs (Acevedo-Whitehouse and Cunningham 2006).…”
Section: Introductionmentioning
confidence: 99%